Manikin-based size-resolved penetrations of CE-marked filtering facepiece respirators - Serfozo, Norbert; Ondráček, Jakub; Otáhal, Petr; Lazaridis, Mihalis; Ždímal, Vladimír (Journal of occupational and environmental hygiene, 2017)
The purpose of this manikin-based study was to determine the percentage penetrations of nine CE-marked filtering facepiece respirator models (two samples from each) from filtering classes FFP1, FFP2, and FFP3 and to demonstrate by an independent measurement method the disadvantages and shortcomings of the currently valid European Norm (EN 149:2001) for filtering facepieces. All of the filtering facepieces were evaluated size-selectively in an experimental chamber using charge-neutralized monodisperse ammonium sulfate in 9 sizes ranging from 20-400 nm of count median diameter (CMD) under flowrate of 95 L/min. The results were then compared to the previous study concerning penetrations of 47-mm diameter filters cut from the filtering material of identical filtering facepieces. Although these two experimental methods for measuring penetrations of filtering materials from filtering facepieces are in good agreement (R2 = 0.91), the results show within-respirator variations in all three filtering classes (5.5-19.3% for all FFRs in FFP1, 2.8-8.5% in FFP2, and 0.1-2.8% in FFP3). The most penetrating particle size (MPPS) in this study was found to be in the range of 25-65 nm (CMD), which is in agreement with the range of 30-60 nm found in the previous study. Moreover, 7 out of 9 FFR models reached higher penetrations from manikin-based respirator measurements than during measurements of filters from the respective respirators. Furthermore, penetration levels increased up to ∼50% when the respirator was not sealed around the face of the manikin, indicating that the real protection level provided by these filtering facepieces may be even lower if the respirator does not fit perfectly. Considering that poor filtration efficiency and poor fit may increase under real work conditions, the particle penetration is even higher than was found in this study. Therefore, the CE-marked respirators examined in this study may not be efficient in providing the expected level of protection for workers exposed to nanoparticles.
Keywords: modely anatomické rozkládací; Inhalation Exposure; inhalační expozice; síran amonný; pevné částice; Filtration; Manikins; Particle Size; Respiratory Protective Devices; nanočástice; Nanoparticles; Materials Testing; testování materiálů; Particulate Matter; velikost částic; prostředky na ochranu dýchání; Ammonium Sulfate; filtrace